Test case prioritization approach for sequence of events using complexity factor - Ja'afar, Emyreema (2018)
Test case prioritization (TCP) is a method to prioritize and schedule test cases. The technique is developed in order to run test cases of higher priority for minimizing the time, cost and effort during software testing phase. Complexity is one of the factors that affect the effectiveness of the TCP. However, the existing techniques for measuring complexity have some limitations. This is due to inaccuracy in finding the weightage value for complexity as the value will be used to determine the test case prioritization. This study aims on proposing a TCP approach using complexity factor in order to get a better accuracy in prioritizing the test case for event sequences. The study use a Branch Coverage Expectation (BCE) complexity measurement that been proved empirically in the previous research. In this study, an automate tool is developed to calculate the BCE value using a Visual Basic and Microsoft Access. Average Percentage Fault Detection metric is used to evaluate the proposed approach. The fault matrix was build based on the testing done in Junit Eclipse. Based on the results, it shows that by only using complexity factor solely to determine the test case prioritization has does not improve the effectiveness of TCP approach. It is suggests that the proposed approach need to be combined with other factor(s) in order to improve the effectiveness of TCP.